Synthesis and Structural Studies of Some Macrocyclic Complexes of Ni(II) of Bioinorganic Relevance - Ambwani, Jitendra; Bansal, N.L.; Rani Sharma, Mamta (Asian Journal of Chemistry, 2010)
Two new macrocyclic complexes have been synthesized by condensing 2,6-diacetyl pyridine/2,6-pyridine dicarbonyl dichoride with dithiodipropionic acid dihydrazide in presence of Ni(II) ions. The complexes liave the formulae Ni[DPDTDH](BF4)2 and Ni[DCDTDH](BF4)2 (where [DPDTDH] = 2,6-diacetyl pyridine-N-dithio-dipropionic acid dihydrazone and [DCDTDH] = 2,6-pyridine dicarbonyl dichloride-N-dithio-dipropionic acid dihydrazone) have been synthesized. The structure of the complexes has been elucidated on the basis of IR and electonic spectral data, magnetic properties and conductivity studies. All these complexes have been tested for their antimicrobial activity against bacteria E. coli and fungal strains C. albicans and A. flavus. The biological activity of metal chelates was found to be much more as compared to the macrocyclic ligand fragments and individual metal ions.